The EDUKASI PENGGUNAAN TAS RANSEL BERBEBAN BERAT TERHADAP POSTUR TUBUH DAN MALOKLUSI DI SMPN 56 SURABAYA: EDUKASI PENGGUNAAN TAS RANSEL BERBEBAN BERAT TERHADAP POSTUR TUBUH DAN MALOKLUSI DI SMPN 56 SURABAYA - Dyah Parmasari, Wahyuni; Soekanto, Ayly; Devi Dwi Rianti, Emilia; Sahadewa, Sukma (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
In the daily activities of students in Indonesia, they require the use of bags to carry school books. There are various types of bags nowadays, one of which is often used is the backpack model. Every day teaching and learning activities are very busy, resulting in students bringing various school necessities. For example, textbooks, changes to school clothes, extra-curricular activities and so on, so that the backpack carried by each student becomes heavy or excessively burdened. This is something that students carry with them every day and especially for students aged 10-15 years, where this age is the golden period for growth and development and will have an influence on the formation of body posture. If the student's knowledge is lacking, this will result in asymmetry in body posture, and if left untreated, this will result in back pain and sceliosis. Methods Respondents were taken randomly as many as 78 students from a total of 225 students. Respondents were given a pretest before the counseling and a posttest after the counseling, then a presentation of the student's knowledge level was produced. Results and Discussion There was a significant increase after education was held for students, namely before the education was carried out there was a visible increase of 5%. Conclusion There is an increase in educational knowledge about the habit of using heavy backpacks on body posture and malocclusion at SMPN 56 Surabaya.